If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (2x + 4)(5x + 5) = 0 Reorder the terms: (4 + 2x)(5x + 5) = 0 Reorder the terms: (4 + 2x)(5 + 5x) = 0 Multiply (4 + 2x) * (5 + 5x) (4(5 + 5x) + 2x * (5 + 5x)) = 0 ((5 * 4 + 5x * 4) + 2x * (5 + 5x)) = 0 ((20 + 20x) + 2x * (5 + 5x)) = 0 (20 + 20x + (5 * 2x + 5x * 2x)) = 0 (20 + 20x + (10x + 10x2)) = 0 Combine like terms: 20x + 10x = 30x (20 + 30x + 10x2) = 0 Solving 20 + 30x + 10x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '10'. 10(2 + 3x + x2) = 0 Factor a trinomial. 10((2 + x)(1 + x)) = 0 Ignore the factor 10.Subproblem 1
Set the factor '(2 + x)' equal to zero and attempt to solve: Simplifying 2 + x = 0 Solving 2 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + x = 0 + -2 Combine like terms: 2 + -2 = 0 0 + x = 0 + -2 x = 0 + -2 Combine like terms: 0 + -2 = -2 x = -2 Simplifying x = -2Subproblem 2
Set the factor '(1 + x)' equal to zero and attempt to solve: Simplifying 1 + x = 0 Solving 1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + x = 0 + -1 Combine like terms: 1 + -1 = 0 0 + x = 0 + -1 x = 0 + -1 Combine like terms: 0 + -1 = -1 x = -1 Simplifying x = -1Solution
x = {-2, -1}
| 2(3x-2)-3(x+1)=3 | | (C-2)(C-5)= | | y[n]-0.5*y[n-2]=0 | | 24/2=4/2x | | 44=2(4+3x)+2(4+5x) | | 2x(x+e)=3e(x+e) | | 162=2xsquared | | 4s^2+19=12s | | x/y=2.727272 | | 10x-x^2=5 | | 10x-y^2=5 | | 3+4x-10=17 | | N(14+6)=22 | | (a+1)(a*2+3a+1)= | | x^2-61.28x=2000 | | 15+3y=51-y-y-y | | 16-7m=30 | | 5-3y+5y=-8+6+9y | | -(x-1)=x-5 | | 64-32y=55-35y | | 27=5-2x | | 7+91x=52x+3 | | -2(x-5)=10-3x | | 6x-3x(x-1)=21 | | 2x^2+2y-1=0 | | 2cosx+4sinx=3 | | 16x-5y=125 | | 2y-4=29 | | y^2+11y+49=4 | | x((3x-3)(2x-8)+(2x+2)(3x+1))=(5x-5)(3x+1)(2x-8) | | ln(x)=-x+2 | | x^2+y^2-2y=3 |